Infrastructures of Freedom Public Light and Everynight Life on a Southern City's Margins - Briers, Stephanie (De Gruyter, 2023)
Infrastructures of Freedom sheds light on the impact of inadequate public lighting in self-built communities in Cape Town. In democratic South Africa, where infrastructure provision still reflects deeply embedded notions of citizenship, informal neighborhoods with minimal infrastructure provision face challenges beyond access to basic services and opportunities. Fear, the feeling of being forgotten, and living in undignified conditions are among the powerful experiences darkness brings about in these neighborhoods. The book not only reveals these experiences of everynight life, but takes a step further: it considers how the co-production of a solar public lighting project within a community improved everynight life and suggests ways for infrastructure to more successfully articulate citizenship.